HUBUNGAN PENGETAHUAN IBU MENYUSUI TENTANG PEMBERIAN ASI EKSLUSIF DENGAN TINDAKAN DALAM PEMBERIAN ASI EKSLUSIF PADA BAYI DI WILAYAH KERJA PUSKESMAS POOPO - Rombon, Savsenko; Sri Purwanti, Anik (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Exclusive breast milk (ASI) has an important role in the growth and development of babies. Nursing mothers' knowledge about the importance of exclusive breastfeeding can influence their actions in providing breast milk to their babies. In the Poopo Health Center working area, there are still mothers who are not optimal in providing exclusive breastfeeding. Objective: This study aims to determine the relationship between breastfeeding mothers' knowledge about exclusive breastfeeding and actions in providing exclusive breastfeeding to babies in the Poopo Health Center working area. Method: This research uses quantitative methods with a cross-sectional design. The research sample consisted of 17 breastfeeding mothers who were randomly selected in the Poopo Health Center working area. Data collection was carried out through a questionnaire that measured mothers' knowledge and actions in providing exclusive breastfeeding. Data analysis used statistical tests with a significance level of p-value < 0.05. Results: The results of the study show that there is a significant relationship between breastfeeding mothers' knowledge about exclusive breastfeeding and their actions in giving exclusive breastfeeding to babies (p-value = 0.002). Conclusion: Breastfeeding mothers' knowledge about exclusive breastfeeding is significantly related to their actions in providing exclusive breastfeeding to babies. Therefore, it is important to increase the knowledge of breastfeeding mothers through education and counseling so that coverage of exclusive breastfeeding can increase.